The Determination of Ṭalāq Timing: A Comparative Study Between the Compilation of Islamic Law and the Shafi’i School Scholars - Alfi, Alfi; Choeri, Imron; Rosyad, Amrina (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study examines the differences in the determination of the timing of ṭalāq between the Compilation of Islamic Law (KHI)—as a codified representation of Islamic law in Indonesia and the views of classical scholars, particularly those of the Shafi’i school. The focus of the study lies in how each legal system defines the moment when ṭalāq is considered valid and legally effective, as well as its legal implications on the rights of husbands and wives and the integrity of the family institution. This research adopts a juridical-normative approach and applies a descriptive-analytical method, drawing from literature reviews of classical fiqh texts, statutory regulations, and relevant scholarly journals. The findings indicate that, according to the Shafi’i school, ṭalāq is considered to take effect immediately upon the husband’s pronouncement of a valid ṭalāq, whether expressed explicitly (ṣarīḥ), which requires no accompanying intention, or implicitly (kināyah), which must be accompanied by intent. In this context, the legal effect of ṭalāq does not depend on court proceedings or administrative registration; rather, it hinges on the husband’s verbal expression and intention as the substantive conditions for validity. Conversely, under the KHI, ṭalāq is only deemed valid if it is formally declared by the husband before a panel of judges during a Religious Court session. Any ṭalāq pronounced outside this official mechanism, such as privately or informally, has no legal standing, even if stated verbally by the husband. This divergence reflects a shift in legal paradigms: from a substantive-textual approach in classical jurisprudence to a formal-procedural approach in contemporary, institutionalized Islamic law. The KHI emphasizes women’s protection and legal certainty within the household, while the Shafi’i school focuses more on the authority of the husband and the spiritual-legal meaning of ṭalāq. Therefore, this study highlights the importance of harmonizing classical fiqh values with the demands of modern legal frameworks, ensuring that Islamic law remains contextual, just, and responsive to the evolving dynamics of contemporary society.